2017
DOI: 10.3126/jssn.v20i2.24377
|View full text |Cite
|
Sign up to set email alerts
|

High risk pregnancy and Fetal outcome at Shree Birendra Hospital

Abstract: Introduction: High risk pregnancy is a major cause of morbidity and mortality in a developing country. These patients are recognized in the initial prenatal office visit as they have a poor obstetrical history or a well recognized medical complication however; pregnancy becomes high risk because they develop unexpected complications in the course of otherwise normal pregnancies. The objective of this study is to identify various type of high risk pregnancy and fetal outcome. Methods: This was a descripti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…4 Similarly study conducted in Shree Birendra military hospital, Nepal (2017), reported previous lower segment cesarean section as the most common identified high risk pregnancy in 34 (5.43%) cases followed by young primi gravida (3.19%), and breech (2.23%). 5 In contrast, study done in Pakistan (2017) found that among the systemic diseases, anemia (37%) was the most common risk factor followed by hypertension (20%). Obstetrical hemorrhage (p/v bleeding) was the most prevalent complication of existing pregnancy, which contributes to the pregnancy being high risk.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…4 Similarly study conducted in Shree Birendra military hospital, Nepal (2017), reported previous lower segment cesarean section as the most common identified high risk pregnancy in 34 (5.43%) cases followed by young primi gravida (3.19%), and breech (2.23%). 5 In contrast, study done in Pakistan (2017) found that among the systemic diseases, anemia (37%) was the most common risk factor followed by hypertension (20%). Obstetrical hemorrhage (p/v bleeding) was the most prevalent complication of existing pregnancy, which contributes to the pregnancy being high risk.…”
Section: Discussionmentioning
confidence: 95%
“…3,4 This study is not in agreement with the studies done in Nepal at Shree Birendra military hospital (2017),and Koshi Hospital in the Morang district (2020), where low prevalence of high risk pregnancy was identified 15.81% and 14.4% respectively. 5,6 Similarly, studies conducted in India at Puducherry (2019) and Haryana (2020) showed low prevalence of 18.3% and 12.73% respectively. 7,8 Free Full Text Articles are Available at www.jnma.com.np Moreover, higher prevalence of 40.5% and 34.3% highrisk pregnancy was seen in the studies done in India at Uttarpradesh (2020) and Delhi (2023) respectively.…”
Section: Discussionmentioning
confidence: 95%
“…There are several possible explanations for the relationship between high-risk pregnancy and subsequent complications and we attempt to mention a few of them. A high-risk pregnancy might have persisted throughout the pregnancy journey, leading to complications during labour and delivery 20–22. One reason for the possible persistence of the complication might be inadequate management of the complication.…”
Section: Discussionmentioning
confidence: 99%
“…One reason for the possible persistence of the complication might be inadequate management of the complication. Furthermore, perhaps women who are high risk might have lack access to or usage of ANC services, which can lead to inadequate management of potential complications during pregnancy, labour or delivery 20 21. It is important to identify high-risk pregnancies early, during the first ANC visit, to provide appropriate obstetric and intrapartum monitoring and care to ensure maternal and neonatal survival.…”
Section: Discussionmentioning
confidence: 99%
“…High risk pregnancy is defined as the one in which there is presence of maternal or fetal factor that affects the 1 pregnancy outcome -maternal or perinatal or both. High risk pregnancy cons tutes about 15 to 40 % of cases of [2][3][4][5][6][7][8] pregnancy based on different studies. Maternal complica ons have been reported to be increased in pregnancies 4,7,9 complicated by high risk factors.…”
Section: Introductionmentioning
confidence: 99%